Science-related aspirations of career based on learning content in upper secondary level - Mohd Razimi Husin; Hishamuddin Bin Ahmad; Muhammad Bazlan Bin Mustafa; Ismail Yusuf Panessai; Ramlan Ramlan (International Journal of Evaluation and Research in Education (IJERE), 2020)
This study used qualitative approach which involves interviews that are analyze using Nvivo software. Qualitative approach which uses phenomenological design to reflect on the experience of the former students towards their experience and learning contents of secondary school upper level science core subject which impacted their career aspirations today. Twelve experience workers were selected through purposeful sampling. The results show that most respondent just got C for their Science Subject in Malaysian Certificate of Education (MCE). The certain techniques including the use of the learning aids and room were very effective; while contents of fluid and organs were much related to works. This study has revealed the effective techniques of learning experiences that beneficial to all educators.